ESTIMASI CADANGAN KARBON DIATAS PERMUKAAN TANAH PADA BEBERAPA TINGKAT KERAPATAN VEGETASI DI DESA KIRAM KABUPATEN BANJAR - Lusiana Dewi; Rina Kanti; Abdi Fithria (Jurnal Sylva Scienteae, 2024)
One of the causes of global warming is human activities that result in increased greenhouse gas emissions. Vegetation density has many benefits, especially maintaining the balance of the ecosystem by absorbing CO2 contained in the atmosphere from the air and producing oxygen. This study aims to analyze the estimation of biomass, stored carbon reserves, and the economic value of aboveground carbon reserves at several levels of vegetation density in Kiram Village, Banjar Regency. The method of determining plot points using purposive sampling involves a plot size of 20 m × 100 m. There are two plots at each density level. Data collection at the seedling, sapling, pole, tree, and necromass growth levels using non-destructive methods. Sampling of undergrowth and litter was carried out by destructive methods, followed by curing in the laboratory. The results of this study show that at a low density level, the estimated biomass value is 3,779.254 tons and the estimated carbon stock is 1,776.249 tons. Medium density level with an estimated biomass value of 57,204.497 tons and an estimated carbon stock of 26,886.113 tons. High density level with an estimated biomass of 107,392.051 tons and an estimated carbon stock of 50,474.264 tons. Very high density level, with an estimated biomass of 289,653.703 tons and an estimated carbon stock of 136,137.240 tons. The economic value of the total carbon stock in Kiram Village, Banjar Regency, amounted to IDR 15,951,793,560.22.Salah satu penyebab terjadinya pemanasan global adalah aktivitas manusia yang mengakibatkan peningkatan emisi gas rumah kaca. Kerapatan vegetasi memiliki banyak manfaat terutama menjaga keseimbangan ekosistem dengan menyerap CO2 yang terdapat di atmosfer dari udara dan menghasilkan oksigen. Penelitian ini bertujuan untuk menganalisis estimasi biomassa, cadangan karbon tersimpan dan nilai ekonomi cadangan karbon yang terdapat di atas permukaan tanah di beberapa tingkat kerapatan vegetasi di Desa Kiram Kabupaten Banjar. Metode penentuan titik plot menggunakan purposive sampling dengan ukuran plot 20 m × 100 m terdapat 2 plot pada masing – masing tingkat kerapatan. Pengambilan data pada tingkat pertumbuhan semai, pancang, tiang, pohon dan nekromassa menggunakan metode non destructive. Pengambilan sampel tumbuhan bawah dan seresah dilakukan dengan metode destructive kemudian dilakukan pengovenan di laboratorium. Hasil dari penelitian ini menunjukan pada tingkat kerapatan rendah nilai estimasi biomassa 3.779, 254 ton dan estimasi cadangan karbon 1.776,249 ton. Tingkat kerapatan sedang dengan nilai estimasi biomassa 57.204,497 ton dan estimasi cadangan karbon 26.886,113 ton. Tingkat kerapatan tinggi nilai estimasi biomassa 107.392,051 ton dan estimasi cadangan karbon 50.474,264 ton. Tingkat kerpatan sangat tinggi dengan nilai estimasi biomassa 289.653,703 ton dan estimasi cadangan karbon 136.137,240 ton. Nilai ekonomi cadangan karbon total di Desa Kiram, Kabupaten banjar sebesar Rp 15.951.793.560,22.